Freezing behaviour of impact droplet on cooled super-hydrophilic mesh and silicon wafer - Chang, Chern Jie (Nanyang Technological University, 2020)
The freezing behaviours of water droplets at room temperature impacting a cold superhydrophilic silicon wafer substrate, and a unique pressed-mesh substrate are investigated experimentally in this paper. This paper reports that the stage of impact in which nucleation begins determines the final freezing morphology. The various freezing phenomena are explored, and explanations are proposed. The results are clustered graphically to produce a regime map that may allow prediction of freezing behaviour in future scenarios. A brief extension of the investigation is conducted on a novel pressed-mesh substrate (stainless steel mesh pressed into sheet aluminium) and it is shown that macro-scale mesh properties such as a higher open-area-ratio leads to lesser droplet spreading and more bubble entrapment on impact. This bubble entrapment leads to lower heat transfer rate and slower freezing, showing that macro-scale geometrical features can be used to influence freezing rate.